2011
DOI: 10.1002/path.2831
|View full text |Cite
|
Sign up to set email alerts
|

Ski, a modulator of wound healing and scar formation in the rat skin and rabbit ear

Abstract: We recently demonstrated that Ski is a novel wound healing-related factor that promotes fibroblast proliferation and inhibits collagen secretion. Here, we show that increasing local Ski expression by gene transfer not only significantly accelerated wound healing by relieving inflammation, accelerating re-epithelialization and increasing formation of granulation tissue, but also reduced scar formation by decreasing collagen production in rat dermal wounds. Similarly, ski gene transfer accelerated wound healing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 55 publications
0
47
0
Order By: Relevance
“…scxk (Yu) 2002-0002, grade II). pSuper-c-Ski-RNAi was made previously [11], which has been confirmed to successfully knockdown Ski expression both in rat fibroblasts and wound tissues in our recent study [10,11]. Antibodies specific to Ski (sc-9140), PPARδ (sc-7197), β-actin (sc-1616), PPARδ agonist GW501516 (sc-202642) and antagonist GSK0660 (sc-203985) were purchased from Santa Cruz Biotechnology (Santa Cruz, CA, USA).…”
Section: Animals and Reagentsmentioning
confidence: 66%
See 1 more Smart Citation
“…scxk (Yu) 2002-0002, grade II). pSuper-c-Ski-RNAi was made previously [11], which has been confirmed to successfully knockdown Ski expression both in rat fibroblasts and wound tissues in our recent study [10,11]. Antibodies specific to Ski (sc-9140), PPARδ (sc-7197), β-actin (sc-1616), PPARδ agonist GW501516 (sc-202642) and antagonist GSK0660 (sc-203985) were purchased from Santa Cruz Biotechnology (Santa Cruz, CA, USA).…”
Section: Animals and Reagentsmentioning
confidence: 66%
“…However, the transcriptional or translational modulation of Ski gene in these conditions is not clear. Our recent study has demonstrated that Ski is a new tissue repair-related gene, which is mainly expressed in fibroblasts and modulates wound healing and scar formation by regulating TGF-β-dependent or -independent pathway [10][11][12]. Accordingly, it is essential to investigate the endogenous or exogenous factors to regulate Ski expression or function, which has the potential to provide a novel strategy to accelerate wound healing via modulating Ski-mediated signaling and effects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cDNA and siRNA can serve as controls for each other in recovery experiments. 138,139 More importantly, siRNA posttranscriptional modifications have been applied to achieve transient local ablation of malignant genes at different phases of wound healing.…”
Section: 81mentioning
confidence: 99%
“…The formation of hypertrophic scars that dominates the socket contracture tissue is a deviation of wound healing in the form of hyperactivity of fibroblast, excessive formation of myofibroblasts and extracellular matrix (ECM) deposition [7,8] TGF-β plays roles in all phases of eye wound healing process by increasing growth factor secretion involved in cell migration, proliferation, ECM deposition and myofibroblast formation. Increased growth factor activity not only leads to an increase in wound healing rate, but also a higher risk for scar formation.…”
Section: Introductionmentioning
confidence: 99%
“…Increased growth factor activity not only leads to an increase in wound healing rate, but also a higher risk for scar formation. Therefore, TGF-β is one of the most potential targets for scarring intervention [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%